Kerr Spatiotemporal Self-Focusing in a Planar Glass Waveguide - Eisenberg, H. S.; Morandotti, R.; Silberberg, Y.; Bar-Ad, S.; Ross, D.; Aitchison, J. S. (Phys. Rev. Lett., 2001)
We observed simultaneous focusing in both space and time for light pulses propagating in a planar waveguide. In particular, 60 fs pulses with a width of 170 μm were injected into a planar glass waveguide in the anomalous dispersion regime. Output pulses as short as 30 fs and as narrow as 20 μm were measured. The results suggest that multiphoton absorption and intrapulse stimulated Raman scattering arrest the spatiotemporal contraction. The results were compared to the pulse evolution in zero and normal dispersion regimes and were shown to be significantly different. All of the experimental results were reproduced by a numerical model.
Publisher: American Physical Society